Persepsi Siswa terhadap Guru Bimbingan dan Konseling dalam Pelaksanaan Layanan Konseling Individu di MAN 6 Jakarta - Savina Nazwa Azzahra; Nurmawati Nurmawati (SENTRI: Jurnal Riset Ilmiah, 2025)
Lack of understanding about individual counseling services among students often leads to negative perceptions of guidance and counseling (BK) teachers. Some students still view BK teachers as figures of discipline enforcement rather than as supportive facilitators for problem-solving. This study aims to explore students' perceptions of individual counseling services at MAN 6 Jakarta, focusing on three aspects: cognitive, affective, and conative. The research employed a qualitative descriptive method, using data collection techniques such as interviews, observation, and documentation. The subjects of the study included six eighth-grade students, one BK teacher, and one vice principal for curriculum. The results showed that in the cognitive aspect, some students had limited understanding of the purpose of individual counseling and still associated the BK room with punishment. In the affective aspect, students initially felt anxious or nervous when invited to counseling sessions but eventually experienced relief and comfort during the interaction. Regarding the conative aspect, only a few students were willing to seek counseling voluntarily, while most preferred to wait for a summons or would only come when overwhelmed. Meanwhile, the BK teacher perceived the students as open and responsive. This indicates a discrepancy between teacher and student perspectives. The findings conclude that students' perceptions of individual counseling are still influenced by stigma and incomplete understanding. Thus, consistent socialization and a humanistic approach are needed to help students view individual counseling as a safe and supportive space for personal growth and problem resolution.